NATIONAL QUALIFICATIONS SYSTEM: A GUARD FOR THE INTEGRATION OF THE LABOR MARKET AND THE EDUCATION SYSTEM - Shikhnazar Sharafaddinov (Zeta Repository, 2023)
This article examines the main reasons for the reforms carried out in the vocational education system, the history of the introduction of the National Qualifications System in our country and its legal basis, as well as the processes associated with ensuring the integration of the labor market and educational services through the maintenance of this system